Development of Adiwiyata-Based Integrated IPS Teaching Materials (Study of Environmental Wetlands and Sustainable Development at SMPN 11 Kota Banjarbaru) - Muhammad Efendi; Arif Rahman Nugroho; Nasir Nayan; Rusdiansyah Rusdiansyah; Ellyn Normelani (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2022)
Teaching materials are a set of learning materials that is arranged systematically to provide a complete mapping (picture) related to the competencies that have been obtained by students in learning activities. The material presented allows students to acquire competencies consistently and systematically and to accumulate the acquired competencies in a complete and integrated manner. The function of teaching materials is to guide the teachers in all learning activites and represent the content of competencies that will be taught to students. The research method used is Research and Development, which is a process or steps to develop a new product or improve an existing product and can be accounted for. The development stages in this study were the Four-D development models which are consisted of 4 stages, namely: (1) the definition stage; (2) the design stage; (3) development stage; and (4) the dissemination stage. The purpose of this study was to determine the student's need for Integrated Social Studies learning which was then integrated with Adiwiyata values-based learning using media (local content) and an inquiry training approach to provide material wealth for students. The results obtained from the research are student responses to teaching modules based on Adiwiyata values are in the valid category with scores above 3 (75%) meaning that this teaching material is very interesting with the presentation of the material based on local content and is up-to-date.